PERAN STRATEGI KOMUNIKASI KRISIS DALAM MEMITIGASI DAMPAK BRAND SWITCHING DAN PENURUNAN HARGA SAHAM AKIBAT BOIKOT KONSUMEN: Studi Kasus Pada Starbucks - Nurdina, Hana; Zahrotul Firdaus, Risya; Ella Nilla Chandra, Yanita; Jati Saputro, Restu; Kurniasari, Ratri; Puspitasari, Nuria (Jurnal Administrasi Profesional, 2025)
The contemporary digital era has fundamentally transformed the business communication landscape, where consumers possess significant power in shaping brand reputation through social media. Starbucks Corporation faced massive boycott waves triggered by political position controversies in late 2023, resulting in market value losses of 11 billion US dollars. This study aims to comprehensively analyze the role of crisis communication strategies in mitigating the impact of Brand Switching and stock price decline due to consumer boycotts using Starbucks as a case study objectThe research employed a quantitative approach with case study design, involving 384 respondents aged 18-30 years through purposive sampling. Research instruments consisted of structured questionnaires with Likert scale 1-5, analyzed using Structural Equation Modeling (SEM) and multiple regression analysis. Results showed low effectiveness of Starbucks' crisis communication (score 2.34/5), with Brand Switching intention reaching 68.2%. Significant negative correlations were found between crisis communication effectiveness with Brand Switching (r = -0.672) and stock volatility (r = -0.445). Maximum stock price decline reached 9.47% with market capitalization falling by 11.2 billion USD. Starbucks' reactive and defensive crisis communication strategy failed to mitigate boycott impacts. Development of crisis communication playbook emphasizing proactive engagement and transparency is recommended, along with implementation of early detection systems based on real-time sentiment analysis.